Inhalational monkeypox virus infection in cynomolgus macaques - Barnewall, Roy; Knostman, Katherine; Fisher, David; Robertson, Ashley; Vales, Pauline; Bigger, John (Frontiers in Cellular and Infection Microbiology, 2012)
An inhalation exposure system was characterized to deliver aerosolized monkeypox virus (MPXV), and a nonhuman primate (NHP) inhalation monkeypox model was developed in cynomologus macaques. A head-only aerosol exposure system was characterized, and two sampling methods were evaluated: liquid impingement via an impinger and impaction via a gelatin filter. The aerosol concentrations obtained with the gelatin filter and impinger were virtually identical, indicating that either method is acceptable for sampling aerosols containing MPXV. The mass median aerodynamic diameter (MMAD) was for individual aerosol tests in the aerosol system characterization and the NHP study ranged from 1.08 to 1.15 µm, indicating that the aerosol particles were of a sufficient size to reach the alveoli. Six cynomolgus macaques (four male and two female) were used on study. The animals were aerosol exposed with MPXV and received doses between 2.51 x 104 to 9.28 x 105 plaque forming units (pfu) inhaled. Four of the six animals died or were euthanized due to their moribund conditions. Both animals that received the lowest exposure doses survived to the end of the observation period. The inhalation LD50 was determined to be approximately 7.8 x 104 pfu inhaled. These data demonstrate that an inhalation MPXV infection model has been developed in the cynomolgus macaque with disease course and lethal dose similar to previously published data.